ยุทธศาสตร์การเสริมสร้างการพึ่งตนเองแบบมีส่วนร่วมในระดับหมู่บ้านโดยยึดหลักปรัชญาของเศรษฐกิจพอเพียง ของหมู่บ้านในจังหวัดหนองบัวลำภู - กันหาชิน พีระ; เป็นสุข วิบูล; นาคะกุล ชาตรี (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาสภาพการพึ่งตนเองและปัจจัยที่มีความสัมพันธ์ต่อการพึ่งตนเองในระดับหมู่บ้าน และเพื่อกำหนดยุทธศาสตร์การเสริมสร้างการพึ่งตนเองแบบมีส่วนร่วมในระดับหมู่บ้านโดยยึดหลักปรัชญาของเศรษฐกิจพอเพียงของหมู่บ้านในจังหวัดหนองบัวลำภู การวิจัยเป็นแบบผสมผสาน (Mixed Methods Research) ผลการวิจัยพบว่าจังหวัดหนองบัวลำภู มีปัญหาการพึ่งตนเองด้านเศรษฐกิจมากที่สุด ยุทธศาสตร์การเสริมสร้างการพึ่งตนเองแบบมีส่วนร่วมในระดับหมู่บ้านโดยยึดหลักปรัชญาของเศรษฐกิจพอเพียงของหมู่บ้านในจังหวัดหนองบัวลำภู ประกอบด้วย 4 ยุทธศาสตร์ คือ ยุทธศาสตร์การพัฒนาความรู้ในการเสริมสร้างเศรษฐกิจชุมชน ยุทธศาสตร์ส่งเสริมความมั่นคงในอาชีพและรายได้ ยุทธศาสตร์พัฒนาระบบการเงินเพื่อสนับสนุนการลงทุนและ ยุทธศาสตร์ส่งเสริมและพัฒนาระบบการตลาด The Strategies Enhancing the Participatory Self - reliance at the Village Level Based on the Sufficiency Economy Philosophy of Villages in Nongbualamphu Province This research aimed at studying the state of self-reliance and factors relating to self-reliance at the village level and setting the strategies enhancing the participatory self-reliance at the village level based on the Philosophy of Sufficiency Economy of villages in Nongbualamphu Province. The design of this research was Mixed Methods Research. Problem of the villages in Nongbualamphu Province was self-reliance on economy. According to the problem, strategies enhancing participatory self-reliance at the village level based on the Philosophy of Sufficiency Economy were set, including 4 strategies. The first strategy was developing knowledge on promoting community economy. The second strategy was promoting the security of occupation and income. The third strategy was developing financial system to support the investment. The fourth strategy was enhancing and improving market system.